2018
DOI: 10.1002/hep.29577
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocyte autophagy contributes to hepatic cystogenesis in polycystic liver disease and represents a potential therapeutic target

Abstract: Autophagy is increased in PLD cholangiocytes, contributes to hepatic cystogenesis, and represents a potential therapeutic target for disease treatment. (Hepatology 2018;67:1088-1108).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…This suggested that the moderate enhancement of autophagy might be beneficial to the culture of stem cells in vitro, which cleared away the impaired cellular components and kept cell homeostasis [ 48 , 49 ]. Moreover, the intensity of autophagy could be regulated by certain drugs, such as rapamycin [ 50 , 51 ] and bafilomycin A1 [ 52 , 53 ]. Since BMSCs are widely applied as seed cells in bone tissue engineering [ 54 ], our study may provide a new strategy to expand BMSCs abundantly in vitro by regulating their autophagy intensity without impairing their self-renewal and pluripotent differentiation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that the moderate enhancement of autophagy might be beneficial to the culture of stem cells in vitro, which cleared away the impaired cellular components and kept cell homeostasis [ 48 , 49 ]. Moreover, the intensity of autophagy could be regulated by certain drugs, such as rapamycin [ 50 , 51 ] and bafilomycin A1 [ 52 , 53 ]. Since BMSCs are widely applied as seed cells in bone tissue engineering [ 54 ], our study may provide a new strategy to expand BMSCs abundantly in vitro by regulating their autophagy intensity without impairing their self-renewal and pluripotent differentiation abilities.…”
Section: Discussionmentioning
confidence: 99%
“…It is protective through enhanced phosphorylation of the pro-survival kinase ERK1/2 [36]. It efficiently inhibited hepatic cystogenesis in the polycystic kidney disease and affected the autophagy process that increased in polycystic liver disease [37]. HCQ is evaluated in cardiac neonatal lupus model and it gives favorable results.…”
Section: Discussionmentioning
confidence: 99%
“…An aberrant relation between intracellular calcium and c-AMP is proposed as the mechanism of liver cyst formation. 3,7 As discussed, tolvaptan reduces c-AMP in cholangiocytes. 9 Although 14 out of 135 ADPKD patients experienced hepatic events in Tolvaptan Efficacy and Safety in Management of Autosomal Dominant Polycystic Kidney Disease and its Outcomes (TEMPO) extension Japan trial, they recovered after the interruption of tolvaptan.…”
mentioning
confidence: 95%
“…Recent studies show that cholangiocyte autophagy, which is associated with activation of the cyclic adenosine monophosphate protein signaling pathway, contributes to cystogenesis in polycystic liver disease. 7 Further, follicle-stimulating hormone (FSH) receptors are seen in biliary epithelial cells from normal and ADPKD patients. 8 FSH increases c-AMP in cholangiocytes, inducing biliary growth via ERK.…”
mentioning
confidence: 99%
See 1 more Smart Citation